Some Thoughts on American Education and on American Teachers - Kneeshaw, Stephen (Teaching History: A Journal of Methods, 1999)
On Memorial Day 1998 the sheriff of Springfield, Oregon, lamented the killing of four people and the wounding of several others by a fifteen-year old student wielding a gun just days before. He expressed the grief that gripped the people of Springfield, the state of Oregon, and the United States. He closed by noting that in his many years in the military and in law enforcement, he had seen the best and the worst in people and in society. What saddened him now, he confessed, was that he was seeing much more of the worst than the best. Springfield was only one of several American communities that witnessed violent killings of students and teachers by students in schools in 1997, 1998, and 1999. The list reads like a cross-country American geography lesson: Pearl, Mississippi; West Paducah, Kentucky; Jonesboro, Arkansas; Springfield, Oregon; Littleton, Colorado; Conyers, Georgia. These towns--all reflecting middle-American values--suffered the worst of the incidents. Parents, teachers, and students fell to bullets fired by students ranging from eleven years into their late teens. Other towns and cities experienced problems with violence (even shootings without deaths), but these were the ones that received the most national attention.